(untitled) (Architecture Image Studies, 2026)
This study aims to analyze the effect of Credit Risk on Bank Stability by considering the mediating role of Profitability and Liquidity Risk in Regional Development Banks (BPD) in Indonesia. The study uses a quantitative approach with a causal-comparative design and utilizes panel data that combines cross-section and time-series data on 27 BPDs registered with the Financial Services Authority during the observation period. The analysis was conducted using Partial Least Squares-based Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software to test the direct and indirect relationships between variables. The results show that Credit Risk has a negative and significant effect on Bank Stability and Profitability, and a significant positive effect on Liquidity Risk. Furthermore, Profitability is proven to have a significant positive effect on Bank Stability, while Liquidity Risk has a significant negative effect on Bank Stability. The main findings of this study indicate that Profitability and Liquidity Risk act as partial mediators in the relationship between Credit Risk and Bank Stability, indicating that the impact of Credit Risk on Stability occurs not only directly, but also through pressure on bank profit performance and liquidity. Specifically in the context of Regional Development Banks, a funding structure dependent on third-party funds and a concentrated regional credit portfolio strengthen the transmission channel of Credit Risk through Liquidity Risk. This research provides theoretical contributions by enriching Financial Stability Theory and Financial Intermediation Theory, as well as practical implications for BPD management and regulators in designing integrated credit and liquidity risk management policies to maintain sustainable banking stability.